Mild mixed-solvent extraction for determination of total mineral oil hydrocarbon contaminants in milk powder products. (15th December 2020) - Liu, Lingling; Li, Bingning; Ouyang, Jie; Wu, Yanwen
Highlights: n -Hexane/isopropanol (3:1) extract total mineral oils in milk powder products. The mixed-solvent extraction avoid the loss of low-boiling-point hydrocarbons. Major part of the mineral oil contamination is derived from sources before packaging. Abstract: A mild mixed-solvent of n -hexane/isopropanol is proposed for extracting total mineral oil hydrocarbons (MOH) from commercial milk powder products. Unlike acid-hydrolysis, the mixed-solvent extraction was performed at ambient temperature and the low-boiling-point hydrocarbons were retained to the greatest extent. After extraction, total MOH was determined by on-line liquid chromatography-gas chromatography with a flame ionization detector (LC-GC-FID). The validation of the proposed extraction method revealed a recovery efficacy of 83.0–107.5% and a limit of quantification of 0.5 mg/kg. Then, the total MOH in ten commercial milk powders was determined and mineral oil saturated hydrocarbons (MOSH)/polyolefin oligomeric saturated hydrocarbons (POSH) were found to be within the range of 0.61–5.46 mg/kg. The comparison of the total and surface MOSH/POSH indicated that a major part of the contamination was derived from sources before packaging. The present study provides a robust method for the extraction and determination of total MOH in milk powders.